PENGARUH JARAK TANAM YANG BERBEDA TERHADAP PERTUMBUHAN ANGGUR LAUT (CAULERPA RACEMOSA) YANG DIBUDIDAYAKAN DENGAN METODE LONGLINE DI DESA TANJUNG BELE, KEC. MOYO HILIR, KAB. SUMBAWA - isnawati isnawati; Saptono Waspodo; Mursal Ghazali (Jurnal Media Akuakultur Indonesia, 2022)
The study aimed to determine the effect of spacing on the growth of sea grapes (Caulerpa racemosa) with the longline method in the village of tanjung bele, moyo sub-district downstream, Sumbawa district. The research was carried out from April to May 2018 in the waters of the village of Tanjung Bele, Moyo sub-district, downstream, Sumbawa district. The method used is the experimental method with Completely Randomized Design (CRD) which consists of three treatment spacing and repeated five times. The treatments are: A (30 cm spacing), B (40 cm spacing), C (50 cm spacing). The data obtained are analyzed using ANOVA. Different spacing treatments provide significantly different growth to absolute growth and specific growth rate Different treatment of spacing gives a significantly different effect so that a further test was carried out with the Tukey HSD. Water quality parameter data were analyzed descriptively. The results showed that the absolute growth of sea wine in treatment A namely 201.87 grams, then treatment B 140.40 grams and treatment C amounted to 130.93 grams, while the specific growth rate of sea wine (Caulerpa racemosa), namely spacing of treatment A has an average value of 5.86%, Treatment B 4.83% and treatment C 4.46%. After further testing of absolute growth and specific growth rate of treatment which had significant differences, namely treatment A with B, A with C, B with C, and C with A. All treatments had significant differences. Water quality measurement results are still in the normal range for the growth of sea grapes.